2019
DOI: 10.1152/ajpregu.00205.2018
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac hypertrophy in mice submitted to a swimming protocol: influence of training volume and intensity on myocardial renin-angiotensin system

Abstract: Exercise promotes physiological cardiac hypertrophy and activates the renin-angiotensin system (RAS), which plays an important role in cardiac physiology, both through the classical axis [angiotensin II type 1 receptor (AT1R) activated by angiotensin II (ANG II)] and the alternative axis [proto-oncogene Mas receptor (MASR) activated by angiotensin-(1–7)]. However, very intense exercise could have deleterious effects on the cardiovascular system. We aimed to analyze the cardiac hypertrophy phenotype and the cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Confirming these findings, ACE2 deficiency was related to impaired physical performance and cardiac and skeletal muscle adaptations to exercise in mice (Motta-Santos et al, 2016). Another recent study showed that swimming training improves the oxidative capacity in mice, and the RAS counter-regulatory axis may exert a role in this process (Soares et al, 2019).…”
Section: Discussionmentioning
confidence: 65%
“…Confirming these findings, ACE2 deficiency was related to impaired physical performance and cardiac and skeletal muscle adaptations to exercise in mice (Motta-Santos et al, 2016). Another recent study showed that swimming training improves the oxidative capacity in mice, and the RAS counter-regulatory axis may exert a role in this process (Soares et al, 2019).…”
Section: Discussionmentioning
confidence: 65%
“…A regulator of the cardiovascular system is the renin-angiotensin system (RAS), a system exhibited on various tissues and cells, which has been established as a key regulator of the body’s hormonal and fluid balance system. The RAS is usually pharmacologically targeted for the management of heart failure [ 34 , 35 , 36 , 37 ], diabetes [ 38 , 39 ], and hypertension/blood pressure control [ 40 , 41 , 42 ]. The main effector of RAS is angiotensin II (AngII), which is produced by angiotensin-converting enzyme (ACE) within the circulation or in ACE-expressed cells [ 43 , 44 , 45 ].…”
Section: Effects Of Taurine On the Cardiovascular Systemmentioning
confidence: 99%
“…Previous studies, especially experimental studies, have shown that physical exercise can reduce the activation of the classic RAS pathway and increase the activation of the components of the counter-regulatory pathway (ACE2/Angio-1-7/MAS) (Figure 2). [7][8][9][10][11][12][13] However, the literature is still scarce about the effects of physical exercise on the ACE2/Angio-1-7/ MAS pathway, mainly on ACE2 (the primary receptor site of SARS-CoV-2). In short, it was shown in rodents that physical exercise increased the expression of MAS receptors in aortas, thereby improving the vasodilatory effect of Angio-1-7.…”
Section: Physical Exercise and The Raasmentioning
confidence: 99%